Winston Field and the Decolonisation of 'British Central Africa': Crossing Racial Divides with Kamuzu Banda and Beyond, 1957-64 - Marmon, Brooks (African studies (Johannesburg), 2025)
This article explores the dynamic terrain of African decolonisation via the interracial diplomacy of a right-wing Southern Rhodesian politician, Winston Field. Initially a parliamentarian in the Federation of Rhodesia and Nyasaland, Field became the Southern Rhodesian prime minister as that Federation collapsed. Despite his conservative views, Field enthusiastically pursued dialogue with the region's anti-colonial nationalists. His most substantial outreach was with Hastings Kamuzu Banda, the Malawian nationalist leader, but he encountered anti-colonial nationalists throughout the Federation and British officials discreetly attempted to connect him to Tanganyika's president, Julius Nyerere. Ultimately, Field's diplomatic outreach exerted minimal impact on the region's political affairs. However, his efforts illuminate several critical issues, including inter-white political competition in Rhodesia; the rise of Field's successor, Ian Smith; Banda's tolerance of reactionary white governments; the blinkered nature of Britain's Rhodesia policy; and the consequences of a split in Zimbabwe's nationalist movement.